CHAIRMANSHIP OF THE REPUBLIC OF KAZAKHSTANIN IN OSCE AS FACTOR STRENGTHENINGS OF ORGANIZATION'S AUTHORITY (International relations and international law Journal, 2016)
The article is devoted the chairmanship of RK on OSCE. The factors which defi ned the chairmanship of Kazakhstan in 2010, initiatives and strategic agenda were considered on this article.
Keywords: OSCE; chairmanship of Kazakhstan